2019
DOI: 10.1371/journal.pone.0226410
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in trait-based and taxonomic macrofauna community structure along a 27-year time-series in the south-eastern North Sea

Abstract: Current research revealed distinct changes in ecosystem functions, and thus in ecosystem stability and resilience, caused by changes in community structure and diversity loss. Benthic species play an important role in benthic-pelagic coupling, such as through the remineralization of deposited organic material, and changes to benthic community structure and diversity have associated with changes in ecosystem functioning, ecosystem stability and resilience. However, the long-term variability of traits and functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 101 publications
1
8
0
Order By: Relevance
“…Several previous studies of both present-day and past benthic assemblages have shown that, contrary to simplistic expectations, loss of species or individuals from an assemblage often results in patterns of species change that conserve trait composition and, so, 'potential' ecological functioning (Cesar and Frid 2012;Frid and Caswell 2016;Caswell and Frid 2017;Meyer and Kröncke 2019;Gammal et al 2020). In the present study, the abundances of the unmanipulated taxa did not measurably respond to the animal additions.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Several previous studies of both present-day and past benthic assemblages have shown that, contrary to simplistic expectations, loss of species or individuals from an assemblage often results in patterns of species change that conserve trait composition and, so, 'potential' ecological functioning (Cesar and Frid 2012;Frid and Caswell 2016;Caswell and Frid 2017;Meyer and Kröncke 2019;Gammal et al 2020). In the present study, the abundances of the unmanipulated taxa did not measurably respond to the animal additions.…”
Section: Discussionmentioning
confidence: 94%
“…This could have limited the scale of the changes observed by partially masking or mitigating the effects of the added taxa. The strength of this effect might be expected to change over time, as different community level processes began to manifest, such as reproduction and recruitment, or vary with seasonal changes in the community and resource availability (Raffaelli and Moller 1999;Underwood 2000;Jenkins and Uyà 2016;Meyer and Kröncke 2019).…”
Section: Discussionmentioning
confidence: 99%
“…During the last decades significant changes and shifts in macrofauna communities in the near-and offshore areas of the south-eastern North Sea (Kröncke et al, 2013;Meyer and Kröncke, 2019) and the Wadden Sea (Schückel et al, 2015;Meyer et al, 2016) occurred. These changes and shifts were linked with changes in the climate system and an increase in SST since the beginning of the 21st century.…”
Section: Cockle Long-term Variability In Relation To Environmental Parametersmentioning
confidence: 99%
“…De Castro‐Català et al, 2020; Wright et al, 2016), and assess ecological change. This is particularly true where changes become evident in the functional rather than taxonomic structure (Gagic et al, 2015; Loreau, 2010; Martini et al, 2021; Meyer & Kröncke, 2019; Winemiller et al, 2015). Such approaches have been applied to micro‐organisms (Šimek et al, 2017), algae (Hoadley et al, 2021), land plants (Kattge et al, 2011, 2020), invertebrates (Worischka et al, 2015), fish (Mérigoux et al, 2001) and amphibians (Lourenço‐de‐Moraes et al, 2020), and across the spectrum of freshwater ecosystems, including rivers (e.g.…”
Section: Introductionmentioning
confidence: 99%